Pure Closed Submodules and Pure Extending Modules - Ibrahim, Omar Hameed; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2025)
In this paper closed submodules and extending modules are generalizing to pure closed submodules and pure extending modules, respectively by using pure submodules. In this work, some properties of these concepts are consideration.